PREDICTION OF LECTURER NEEDS THROUGH STUDY PROGRAM WORKLOADS ANALYSIS REVIEW ON X UNIVERSITY - Ali, Syarif; Setiadi, Iwan Kresna; Kusmana, Agus (International Research of Multidisciplinary Analysis, 2023)
The objective of this research is to determine the right number of lectures needed by the faculties of University X. The research is descriptive—analytical study. Data was collected using secondary data and observation. Beside that, the data was also collected through informants, namely vice deans of the Faculty of Law, Business and Management, Social studies, and Vice Rector for General and Financial affairs. The shortage of lecturers will cause the ineffectiveness in the learning process, besides If the number of lecturers is bigger than the workload, it will create the disguise of unemployment. It is necessary for the University to have lectrurers whose workload comply with regulation. This research analysis between minimum credit point (compulsory) with the lecturer needed. Result suggested: several study programs should recruit more lecturers